PENGEMBANGAN MODUL AJAR STEAM MENGENAL AYAM DENGAN MEDIA SENSORIAL UNTUK PAUD - Oscar Chandra Dinata; Ignatia Esti Sumarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Kindergarten (TK) is included in the Early Childhood Education (PAUD) level which is a form of formal education for children aged 4-6 years. Based on the results of a questionnaire distributed to two Kanisius Kadirojo kindergarten teachers and one Pelita Kasih kindergarten teacher, the researcher obtained information that they needed an example of a teaching module for the STEAM element of the “Real environment” sub-element. Researchers are encouraged to develop teaching modules that discuss the material “Getting to know chickens”, as one of the poultry animals in the environment around children. The objectives of this research are 1) Develop STEAM teaching modules on getting to know chickens with sensorial media for PAUD; 2) Knowing the quality of the STEAM teaching module material to recognize chickens with sensorial media for PAUD. The type of research is Research and Development (R&D) using the ADDIE model with stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects were kindergarten teachers and 28 Kanisius Kadirojo Kindergarten B students. Data collection techniques were obtained through open-ended questionnaires. Data analysis techniques used qualitative analysis and quantitative data. The results of the teaching module validation by three experts received an average score of 3.72 (from a scale of 1-4) meaning “very good.” The trial application of the teaching module from 28 children, 20 children (71%) got the results of “starting to develop (MB)”, and 8 children (28%) got the results of “Developing as expected (BSH).